Study Synthesis of 4-Methyl Octanoic Acid and Ethyl-4-Methyl Octanoic Pheromones Aggregation of Rhino Beetle (Oryctes rhinoceros) Using Mannich Reaction and Claisen Rearrangement - Ahmad Kadir Kilo; Achmad Zainuddin; Darwati Darwati (Jambura Journal of Chemistry, 2019)
4-methyl acid octanoat and ethyl-4-methyl Oktanoat aggregation of kumbang badak (Oryctes rhinoceros Linn) using Mannich's reaction and Claisen rearrangement has been synthesized. The synthesis of compounds includes five phases: synthesis, separation, purification and structure determination. The pure compounds produced from each stage of further synthesis are characterised using mass spectroscopy and infra-red spectroscopy. 4-Methiloctanoic acid synthesis products and ethyl-4-methyloktanoat pheromone aggregation kumbang badak (Oryctes rhinoceros Linn) use Mannich reaction and Claisen rearrangement 50.53% and 63.69% respectively.